Perubahan Sosial Perspektif Pendidikan Islam - Janna, Sitti Riadil (Universitas Islam Negeri Alauddin Makassar, 2024)
Social change is any change in social institutions in a society, which affects its social system, including values, attitudes, and behavioral patterns among groups in society. Social changes have a huge influence on Islamic education in various aspects. This has particular implications that Islamic education as a social institution must be dynamic and open to various changes according to differences in socio-cultural loci and developments over time. Therefore, although historically Islamic education has shown its dynamism in responding to social change, many stereotypes are still attached to typical Islamic education institutions to this day, such as the narrowness of the curriculum, lack of professionalism of teaching staff, and scientific dichotomy.